CHALLENGES OF LEARNING ENGLISH THROUGH MOBILE DEVICES: EFL TEACHERS’ PERSPECTIVES - Zainb Abbas Jawad (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
There has been a growing interest in the use of mobile devices for mobile learning. There is a new branch of students in most schools nowadays who are easily connected to technology and innovative mobile devices. This study aims at investigating EFL teachers’ perceptions concerning mobile devices usage for mobile learning purposes. It also aims at finding out whether or not there are any significant differences between male and female perceptions regarding this new type of learning. To achieve these aims, two instruments have been constructed by the researchers a questionnaire and an interview. The results are discussed and conclusions are drawn at the end of the study.